(untitled) (Medico Legal Update, 2019)
Objectives: This study is narrative research to identify the level of job stress, teach efficiency, and job burnout among middle school teachers in Gangwon-do province and to investigate the effects of job stress on teacher efficacy and job burnout. Method: In total, samples were gained from 59 subjects who teach at middle schools in Y town in Gangwon-do province. Data was collected from April 2 to April 23, 2018. Findings: Results showed that their job stress was significantly higher for shorter years of teaching experiences, homeroom teachers, single, and numerous classes. Although their job stress did not affect teacher efficacy, it served as a variable that gives 31.4% impacts on job burnout. Improvements: Working environment needs to be improved through this study and follow-up research is needed to identify methods of decreasing result variables of job burnout when emotional variables such as job stress are mediated as teacher efficacy.